Intraneural hemangioma of the median nerve: A case report - Doğramacı, Yunus; Kalacı, Aydıner; Sevinç, Teoman Toni; Yanat, Ahmet Nedim (Journal of Brachial Plexus and Peripheral Nerve Injury, 2008)
Hemangiomas of the median nerve are very rare and, so far, only ten cases of intraneural hemangioma of this nerve have been reported in the literature. We present a case of 14-year-old girl who had a soft tissue mass in the region of the left wrist with signs and symptoms of carpal tunnel syndrome. Total removal of the mass was achieved using microsurgical epineural and interfasicular dissection. The symptoms were relieved completely, after this procedure, without any neurologic deficit. On follow-up two years later, no recurrence was observed. Whenever a child or young adult patient presents with CTS the possibility of a hemangioma involving the median nerve should be kept in mind in the differential diagnosis.